Profile of Students’ Scientific Literacy Abilities in Higher Education on Chapter Heat and Temperature - Budiarti, Indah Slamet; Beno, Rosmina; Lumbu, Albert; Viyanti, Viyanti (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Students’ scientific literacy is very important to determine the extent to which students are literate aboutthe scientific concepts that have been learned. Therefore, prospective physics teacher students mustmaster scientific literacy to solve various problems from the real world as individuals and must interact insociety and the environment as social beings. The purpose of this study was to analyze the scientificliteracy skills of students of the 2019 class of physics education study program on chapter heat andtemperature. This type of research used to achieve these objectives is descriptive qualitative withqualitative analysis. The subjects in this study were Lecturers in the basic physics course I and students ofthe 2019 class of physics education study program at Universitas Cenderawasih. Data collectiontechniques used in this study were tests, interviews, and documentation. The results of the research fromthe test instrument showed that the scientific literacy skills of physics education students class 2019 werestill low. The results of the interviews strengthen the findings that there are still many physics educationstudents of 2019 who do not have scientific literacy skills of concepts on chapter heat and temperature.